Firm Performance and the Volatility of Worker Earnings - Juhn, Chinhui; McCue, Kristin; Monti, Holly; Pierce, Brooks (Journal of Labor Economics, 2018)
Using linked employer-employee data for the United States, we examine whether shocks to firm revenues are transmitted to the earnings of continuing employees. While full insurance is rejected, the elasticity of worker earnings with respect to persistent shocks in firm revenues is small and consistent with the notion that firms insulate workers from idiosyncratic shocks. Exploring the heterogeneity of effects, we find the largest elasticity in professional services among employees in the top 5% of their employers’ earnings distribution, suggesting that in certain jobs performance pay may be a countervailing force to wage insurance.